Do Budget Deficits Raise Interest Rates in Nepal? - Paudyal, Shoora B. (NRB Economic Review, 2013)
This paper examines short term and long term relationship between nominal interest rates and budget deficits for Nepal using the data for 1988 to 2011. Engle and Granger Error Correction Mechanism (ECM) is applied for the analysis. The regression results show that budget deficits and budget deficits- GDP ratio do not have significant effects on nominal interest rates in Nepal. So, budget deficits in Nepal are interest rates neutral. We come to the conclusion that budget deficits are not crowding out the private investment in this country. However, the deficits have been increasing the burden of loans financing current consumption at the expense of the future consumption, which will have serious implications on the growth of economy.